2017
DOI: 10.3390/inorganics5030052
|View full text |Cite
|
Sign up to set email alerts
|

Pybox-Iron(II) Spin-Crossover Complexes with Substituent Effects from the 4-Position of the Pyridine Ring (Pybox = 2,6-Bis(oxazolin-2-yl)pyridine)

Abstract: Spin-crossover (SCO) behavior of a series of [Fe(X-pybox) 2 ](ClO 4 ) 2 was investigated, where X-pybox stands for 4-X-substituted 2,6-bis(oxazolin-2-yl)pyridine with X = H, Cl, Ph, CH 3 O, and CH 3 S. We confirmed that the mother compound [Fe(H-pybox) 2 ](ClO 4 ) 2 underwent SCO above room temperature. After X was introduced, the SCO temperatures (T 1/2 ) were modulated as 310, 230, and 330 K for X = Cl, Ph, and CH 3 S, respectively. The CH 3 O derivative possessed the high-spin state down to 2 K. Crystallogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Ishida and Kimura [135] reported the solution properties of the Fe(II) complexes of oxazolylpyridines (L33, Scheme 5) with a Cl substituent in the pyridine. Results from the application of the Evans method showed SCO in acetone solution with a T 1/2 at 270 K. The authors concluded, when Cl was substituted by other groups, that electron-donating groups suppress T 1/2 while electron-withdrawing groups raise T 1/2 .…”
Section: Results Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishida and Kimura [135] reported the solution properties of the Fe(II) complexes of oxazolylpyridines (L33, Scheme 5) with a Cl substituent in the pyridine. Results from the application of the Evans method showed SCO in acetone solution with a T 1/2 at 270 K. The authors concluded, when Cl was substituted by other groups, that electron-donating groups suppress T 1/2 while electron-withdrawing groups raise T 1/2 .…”
Section: Results Solutionmentioning
confidence: 99%
“…Ishida and Kimura [135] modified the bpp ligand by replacing pyrazole by oxazoline groups (L33). This new ligand presented several substituents on the pyridine group, one of them being chloride.…”
Section: Methodsmentioning
confidence: 99%
“…The structural distortion is known to regulate T 1/2 to a considerable extent. 16,3032 The solution experiments will afford a better venue for the discussion on the substituent effect.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of substituents will bring about drastic SCO tuning through the covalent bonds, in comparison with the effects through intermolecular interaction from counter ions and/or solvent molecules incorporated. A part of the experimental data has been communicated and clarified to undergo near-room-temperature SCO with X = H, Cl, Ph, CH 3 O, CH 3 S, 16 3-thienyl (3Th), and 4-pyridyl (4Py). 17 The magnetic susceptibility measurements were performed in solution to purge intermolecular interactions and rigid crystal lattice effects, and discussion can be focused on the substituent effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and other groups discovered SCO in [Fe(pybox) 2 ] 2 + complexes and investigated the influences on spin state properties from structural aspects including ligand substituents, counter anions, solvents, and chirality. [34][35][36][37][38][39][40] Owing to the intrinsic advantages of pybox ligands such as facile synthesis, easiness of structural modification with functional units, and excellent luminescent properties, [41][42][43] we attempt to decorate fluorophore, pyrene moiety, to pybox ligand and construct an SCO-fluorescence bifunctional compound. In our design of ligand, the pyrene moiety is conjugately linked to 4positon of pyridine ring of pybox ligand.…”
Section: Introductionmentioning
confidence: 99%